2014
DOI: 10.1016/j.jad.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Is excess mortality higher in depressed men than in depressed women? A meta-analytic comparison

Abstract: a b s t r a c tBackground: It is not well-established whether excess mortality associated with depression is higher in men than in women. Methods: We conducted a meta-analysis of prospective studies in which depression was measured at baseline, where mortality rates were reported at follow-up, and in which separate mortality rates for men and women were reported. We conducted systematic searches in bibliographical databases and calculated relative risks of excess mortality in men and women. Results: Thirteen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 45 publications
7
46
0
8
Order By: Relevance
“…While our results found women demonstrated the largest losses of life expectancy, other studies on mortality risk and life expectancy according to depression status found that men had the greater mortality risk or loss of life expectancy. 11,17,19,20 However, most of these studies tended to focus on elderly or older adult populations that likely have a different risk profile than the full adult population. Indeed, Shah et al 41 assessed both sex and age differences in the association of depression with mortality and found significant depression-age-sex interactions: mortality risk increased for men as age increased above 55 years while the inverse was found for women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While our results found women demonstrated the largest losses of life expectancy, other studies on mortality risk and life expectancy according to depression status found that men had the greater mortality risk or loss of life expectancy. 11,17,19,20 However, most of these studies tended to focus on elderly or older adult populations that likely have a different risk profile than the full adult population. Indeed, Shah et al 41 assessed both sex and age differences in the association of depression with mortality and found significant depression-age-sex interactions: mortality risk increased for men as age increased above 55 years while the inverse was found for women.…”
Section: Discussionmentioning
confidence: 99%
“…10 Potential mechanisms for the relationship between depression and physical disease include immune and endocrine dysregulation and inflammatory processes. 11 Depression has also been associated with an increased risk of mortality in general community populations, as well as in patient populations with chronic illnesses such as coronary heart disease, cancer, diabetes and stroke. 11 There are likely reciprocal effects between depression and disease, with depression being a risk factor for, and a sequela of, disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Il a également été prouvé, outre ces effets négatifs directs, que la dépression augmente le risque de coronaropathie 7 , d'accident vasculaire cérébral 8 et de cancer 9 , ainsi qu'un déclin du fonctionnement physique 10 . Les mécanismes potentiels de la relation entre la dépression et la maladie physique relèvent notamment du dérèglement des systèmes immunitaire et endocrinien et des processus inflammatoires 11 . La dépression a aussi été associée à un risque accru de mortalité, que ce soit dans l'ensemble de la population ou chez les patients atteints de maladies chroniques comme les coronaropathies, le cancer, le diabète ou les AVC 11 .…”
Section: Points Saillantsunclassified